2020
DOI: 10.1016/j.jhealeco.2020.102349
|View full text |Cite
|
Sign up to set email alerts
|

Not only in my genes: The effects of peers’ genotype on obesity

Abstract: Any opinions expressed in this paper are those of the author(s) and not those of IZA. Research published in this series may include views on policy, but IZA takes no institutional policy positions. The IZA research network is committed to the IZA Guiding Principles of Research Integrity. The IZA Institute of Labor Economics is an independent economic research institute that conducts research in labor economics and offers evidence-based policy advice on labor market issues. Supported by the Deutsche Post Founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…These effects may, however, dissipate over time. For instance, [ 47 ] find that social-genetic effects on obesity induced by interactions with high school grade-mates are relevant for girls in adolescence, but they dissipate as they grow into adulthood.…”
Section: Resultsmentioning
confidence: 99%
“…These effects may, however, dissipate over time. For instance, [ 47 ] find that social-genetic effects on obesity induced by interactions with high school grade-mates are relevant for girls in adolescence, but they dissipate as they grow into adulthood.…”
Section: Resultsmentioning
confidence: 99%
“…These effects may, however, dissipate over time. For instance, PLOS ONE [47] find that social-genetic effects on obesity induced by interactions with high school grademates are relevant for girls in adolescence, but they dissipate as they grow into adulthood.…”
Section: Genetic Influence On Bmi Along the Life-cycle: General Patternsmentioning
confidence: 99%
“…As for the genetic components, Dolton and Xiao (2015), Locke et al (2015), Herrera et al (2011), Savona-Ventura and Savona-Ventura (2015), Biroli (2015), Cawley et al (2017) and Brunello et al (2019) consider that part of obesity is transmitted through this route, so the presence of parents or family members with obesity makes children more likely to suffer from it. In this sense, Atella et al (2008), d'Hombres (2005, 2007), Norton and Han (2008), Kortt and Leigh (2010), Lindeboom et al (2009), Cawley et al (2005), Cawley (2000Cawley ( , 2004, Shimokawa (2008), von Hinke Kessler Scholder et al 2010 Conley (2009) have shown that the current knowledge of genetics and its uses in the social sciences is debatable, as there is not enough knowledge to know if the genes related to obesity are not related to other components which are in turn related to the employment and productivity of people.…”
Section: Previous Literaturementioning
confidence: 99%